Penyaluran Zakat Kepada Pelajar Pondok Pesantren dalam Perspektif Fiqh Syafi’iyyah - Karimuddin (Cyber Media Indonesia, 2022)
Zakat is a certain type of property whose owner is required to distribute it to the mustahiq who have been determined by syara'. The determination of mustahiq or groups who are entitled to receive zakat has been determined in the Qur'an, namely faqir, poor, 'amil, mu'allaf, mukatab (slave), gharim, sabilillah, and ibn sabil. The phenomenon that occurs in some communities, especially in Aceh, is that zakat is also distributed to Islamic boarding school students or santri, while these students are not included in the group entitled to receive zakat as mentioned above. From this phenomenon, the author wants to know further the views of Syafi'iyyah fiqh regarding the distribution of zakat to students or students. This research is a qualitative research that is phenomenological in nature, in analyzing the data the researcher uses content analysis techniques. The results of the study show that Islamic boarding school students or santri can receive zakat if they are included in people who are entitled to receive zakat such as the indigent or poor. Because basically the student of knowledge is not entitled to receive zakat on behalf of the student of knowledge, but it is permissible to accept it if the claimant of knowledge is included in the mustahiq zakat. The seeker of knowledge cannot be categorized into sabilillah because sabilillah in syafi'iyah fiqh are people who take up arms in war because they defend Allah's religion.